Evaluation of varieties of Cenchrus purpureus tolerant to drought under pre-montain conditions - Ray, J. V.; Almaguer, R. F.; Ledea, J. L.; Benítez, D. G.; Arias, R. C.; Roselle, Gillelle (Cuban Journal of Agricultural Science, 2018)
Using a random block design with four replications, the establishment ability of varieties of Cenchrus purpureus tolerant to droughts (CT-601, CT-603 and CT-605) was evaluated. These varieties were obtained by tissue culture from CT-115, which was used as control in a pre-mountain area in Guisa municipality. The experiment was developed in the middle phase of rainy period and beginning of dry period. New varieties showed, together with control, high percentages of sprout under pre-mountain conditions (40-65%) and a sigmoidal growth, fitted to an exponential curve. Absolute growth rate was accelerated from 35 days, with a meseta of values of 2 cm day-1 up to 77 days, except CT-605. Later, an important decrease was verified from 77 up to 120 days with less than 0.5 cm day-1. CT-605 showed higher number of leaves (p≤0.05) and CT-115 had the highest length of internodes and leaves (p≤0.05). In the number of nodes, CT-601 wad superior (p≤0.05). There was no effect of variety on yield of dry matter (DM) and yield values close to 15 t ha-1 of total DM and 4 t ha-1 of DM of leave in the establishment cut were reached. It is concluded that new varieties under pre-mountain conditions show high germination (≥ 50 %) with favorable development and growth. It is recommended to evaluate growth and structure of the new varieties in different moments of development under edaphoclimatic conditions of pre-mountain. Key words: germination, king grass, Pennisetum purpureum, growth, development